Empirical determination of the motion resistance of pneumatic bicycle wheels for on and off-road performance - Akande, Fatai Bukola; Ahmad, Desa; Othman, Jamarei; Sulaiman, Shamsuddin; Fashina, Adepoju B. (Academic Journals, 2010)
Four pneumatic bicycle wheels of diameters 405 mm (16'), 510 mm (20'), 610 mm (24') and 660 mm (26') were tested on three different test surfaces (paved surface, grass field and tilled (sandy-clay loam) soil at selected tyre inflation pressures of 276 kPa (40 psi), 337.5 kPa (50 psi) and 414 kPa (60 psi) with varied (added) dynamic loads of 98.1 N (10 kg), 196.2 N (20 kg), 392.4 N (40 kg) and 588.6 N(60 kg) respectively. The motion resistances of these wheels at various dynamic loads and the selected inflation pressures were compared, to identify the wheel with the lowest motion resistance. On all the test surfaces, the 660 mm diameter recorded the lowest motion resistance measured with an average of 16 out of the 36 total number of test outcomes. The 660 mm diameter wheel, if used, has the potential to increase the pull (draft) and can be used in the development of simple, easy to maintain and low-cost agricultural machines with narrow wheels; as traction member for the low-income farmers and the rural dwellers to boost their agricultural productivity.